1995
DOI: 10.1002/polb.1995.090330201
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal sorption of nonionic dyes with two amino groups by various polymers from water

Abstract: Sorption isotherms of nonionic dyes with two amino groups (one anthraquinone dye and two azo dyes) on various polymers from water were measured at 40–90°C (Nylon‐6 and cellulose film) and at 95°C (polyester microfiber). The isotherms were curved, convex to upward, in the range of low dye concentration Cs in water and almost linear in the range of medium to saturated Cs. The isotherms measured at low temperature (40°C for cellulose, 40–60°C for Nylon‐6, and at 95°C for polyester) were satisfactorily described b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Recently, we have found that when some nonionic dyes are sorbed by various polymers (including nylon 6 film) from water at low temperatures (40-.60*C), three kinds of sorption mode operate concurrently, i.e., n = 3 in Equation 1 [ 18]. For this case, the sorption isotherms are accurately expressed by Equation 6, which is Nemst-type partitioning plus two classes of Langmuir sorption, one with very high affinity (&,) and low saturation value (S, ) and the other with low affinity (KL2) and high saturation value (S2): ' When dye sorption follows Equation 6, the dye penetrates the polymer as three distinct species, i.e., dye taken up by partitioning (P species), by the first class of Langmuir sorption (LI species), and by the second class of the Langmuir sorption (L2 species).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we have found that when some nonionic dyes are sorbed by various polymers (including nylon 6 film) from water at low temperatures (40-.60*C), three kinds of sorption mode operate concurrently, i.e., n = 3 in Equation 1 [ 18]. For this case, the sorption isotherms are accurately expressed by Equation 6, which is Nemst-type partitioning plus two classes of Langmuir sorption, one with very high affinity (&,) and low saturation value (S, ) and the other with low affinity (KL2) and high saturation value (S2): ' When dye sorption follows Equation 6, the dye penetrates the polymer as three distinct species, i.e., dye taken up by partitioning (P species), by the first class of Langmuir sorption (LI species), and by the second class of the Langmuir sorption (L2 species).…”
Section: Methodsmentioning
confidence: 99%
“…Because of the high affinity and low saturation value of L j species on the polymer, this species predominates in polymers at very low Cf; the L, species is most strongly sorbed or immobilized in the polymer, and it has very low diffusivity. However, the first class of Langmuir sorption becomes negligible as the temperature rises, e.g., 80-90°C [ 18]. Consequently, the sorption and diffusion behaviors of the dye follow Equations 2 and 3, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Major assumptions for simplifying the calculation of diffusion coefficients are: Constant surface concentrationleftr=a,C=C0at t0left0<r<a,C=f(r)at t=0 Uniform initial concentration throughout the fibre f ( r ) = C 1 , where, C 0 and C 1 denote fibre dye concentration at time t = t 0 and t = t 1 , and r is the radius vector. Equation can be approximated to the Taylor series, by the Shibusava or the Pade approximation methods . However, in the present paper a novel ‘To To’ simple numerical method was used to solve the polynomial equations of degree n, y=Pn(x)=i=0i=naixi=0 (where a is any real number).…”
Section: Theory and Calculationsmentioning
confidence: 99%